2021
DOI: 10.1088/1742-6596/1842/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

Science Batik Ciwaringin: The Implementation of Ethno-STEM PjBL Model in learning Biotechnology at PGSD Students

Abstract: Indonesian batik has been awarded by UNESCO as one of the world’s non-object cultural heritages. And this is a challenge for young generation on how to preserve this culture. The purpose of this research is to implement Biotechnology learning through the Ethno-STEM PJBL model for PGSD students and produce sains batik, so it can triggger the young generation to preserve it. This learning model is a project based learning in analyzing several natural materials as natural dyes for batik, dye-making techniques tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This is because the E-Module is effective in its implementation and can increase the activities of students in the learning process. The use of project-based learning models in learning makes students more active and triggers curiosity in completing the projects they are working on (Sudarmin Momentum: Physics Education Journal, 6 (1), 2022, 101 Yulkifli Yulkifli, Yohandri Yohandri, Hasbi Azis Copyright © 2022, Momentum: Physics Education Journal, ISSN 2548-9127 (print) | 2548-9135 (online) Tresnawati et al, 2021). The use of the Ethno-STEM approach project-based learning model in learning can also hone the skills and creativity of students in doing projects, both individually and in groups (Sumarni & Kadarwati, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This is because the E-Module is effective in its implementation and can increase the activities of students in the learning process. The use of project-based learning models in learning makes students more active and triggers curiosity in completing the projects they are working on (Sudarmin Momentum: Physics Education Journal, 6 (1), 2022, 101 Yulkifli Yulkifli, Yohandri Yohandri, Hasbi Azis Copyright © 2022, Momentum: Physics Education Journal, ISSN 2548-9127 (print) | 2548-9135 (online) Tresnawati et al, 2021). The use of the Ethno-STEM approach project-based learning model in learning can also hone the skills and creativity of students in doing projects, both individually and in groups (Sumarni & Kadarwati, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows the basic knowledge and skills competencies in high school physics subjects following the 2013 Revised 2018 Curriculum on materials relevant to exploration results. In addition to relevance to the curriculum, an Ethno-STEM analysis was carried out because education with an Ethno-STEM-based approach is one of the integrated multicultural-based physics learning (Tresnawati et al, 2021), which is shown in Table 3. This is important for creating contextual physics learning, fun and preserving the game Engklek.…”
Section: Potential Applications In Ethno -Stem Based Physics Learningmentioning
confidence: 99%
“…Ethno-STEM research in Indonesia is conducted on various topics. Figure 2 shows that the topic of learning models is 32% (found in articles by Harto et al (2019), , , , Azalia (2020), Sumarni et al (2020), Tresnawati et al (2021) and an approach of 32% (found in the article , , Izzah et al (2020a), Qori et al (2020), Tresnawati et al (2020, Anugrah (2021)) dominates ethno-STEM research, followed by evaluation and rating of 4% each (found in the article by Izzah et al (2020b) as shown in Figure 2. The findings are generally in line with trends in Science education research during 2018-2022 published in indexed journals and conferences Scopus, which mainly focuses on the topic of learning contexts (Lin et al, 2019).…”
mentioning
confidence: 99%